1999
DOI: 10.1046/j.1365-2141.1999.01242.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of plasminogen activator inhibitor‐1 as inhibitor of platelet and megakaryoblastic cell adhesion

Abstract: Summary. In the present study the ability of plasminogen activator inhibitor type-1 (PAI-1) to interfere with platelet and megakaryoblastic cell adhesion was investigated. Both cell types exhibited integrin-dependent adhesion in a static system, mediated by aIIbb3 on platelets and av-integrins on different megakaryoblastic cell lines, even though they also expressed aIIbb3. In a concentration-dependent manner, active, but not latent or complexed, PAI-1 abrogated cell adhesion onto vitronectin but not onto fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 46 publications
3
24
0
Order By: Relevance
“…The reported M r of circulating 20) is consistent with our results and raises the possibility that the complex, rather than the individual proteins, interacts with other macromolecules. Supporting this concept are studies demonstrating that vitronectin can bind PAI-1 and heparin simultaneously, indicating that PAI-1⅐vitronectin complexes can interact with other molecules (37).Immunolocalization studies demonstrating both PAI-1 and vitronectin on fibrils of fibrin clots formed in vitro or in vivo (38,39) are compatible with the notion that the individual proteins interact with fibrin. Although PAI-1 has been reported to bind directly to fibrin, it has yet to be shown that vitronectin or PAI-1⅐vitronectin complexes interact directly with fibrin.…”
supporting
confidence: 60%
“…The reported M r of circulating 20) is consistent with our results and raises the possibility that the complex, rather than the individual proteins, interacts with other macromolecules. Supporting this concept are studies demonstrating that vitronectin can bind PAI-1 and heparin simultaneously, indicating that PAI-1⅐vitronectin complexes can interact with other molecules (37).Immunolocalization studies demonstrating both PAI-1 and vitronectin on fibrils of fibrin clots formed in vitro or in vivo (38,39) are compatible with the notion that the individual proteins interact with fibrin. Although PAI-1 has been reported to bind directly to fibrin, it has yet to be shown that vitronectin or PAI-1⅐vitronectin complexes interact directly with fibrin.…”
supporting
confidence: 60%
“…Moreover, ectopic expression of DAB2 reversed the siDAB2 effect or, by itself, decreased fibrinogen adhesion of K562 cells. It has been reported that, similar to DAB2, the platelet protein plasminogen activator inhibitor type-1 also possesses anti-adhesive activity and interferes with platelet and megakaryoblastic cell adhesion (39). Due to the fact that DAB2 is highly enriched in platelets, our data imply that the anti-adhesive activity of DAB2 may have its physiological function during platelet activation and aggregation.…”
Section: Ser 24 Phosphorylation Promotes Dab2 Membrane Translocation mentioning
confidence: 53%
“…The figure is a RasMol display based on the coordinates of the x-ray crystal structure of a quadruple mutant of PAI-1 in the active form (33). Please notice that the RasMol program uses the same signature for ␣-helices and the short 3 10 -helix found in the hF/s3A loop. izers was done by competition studies, in which 0.5 or 1 M PAI-1 was preincubated with ANS (100 M), and the fluorescence intensity at 470 nm was then recorded 10 min after addition of nonfluorescent competitors in various concentrations.…”
Section: Methodsmentioning
confidence: 99%